What proportion of people with migraine report postdromal symptoms? A systematic review and meta-analysis of observational studies - Christensen, Rune Häckert; Eigenbrodt, Anna Kristina; Ashina, Håkan; Steiner, Timothy J.; Ashina, Messoud (Cephalalgia, 2023)
Background Postdromal symptoms, following headache resolution, are said to constitute a distinct phase of the migraine attack. We question the evidence for this, with regard both to the nature of such symptoms and to how often they are reported to occur. Methods We searched the Pubmed and Embase databases for relevant articles from their inception until 25 May 2023. We included observational studies recording the proportions of participants with migraine reporting one or more postdromal symptoms or specific individual symptoms. Two reviewers independently screened studies for relevance (agreeing on those to be included), extracted data and assessed risk of bias. Data were analyzed using random-effects meta-analysis to establish the proportions of those with migraine reporting one or more postdromal symptoms, whether among the general population or patients in clinic-based samples. Results Large majorities of participants in either case reported postdromal symptoms: 97% in the only population-based study, and a mean of 86% (95% CI: 71–94%) in four clinic-based studies. The most commonly reported specific symptoms were fatigue (52%; 95% CI: 44–60%), concentration difficulties (35%; 95% CI: 14–65%) and mood changes (29%; 95% CI: 9–64%), none of these being clearly described. These estimates could not be considered reliable: they were subject to substantial study heterogeneity, none of the studies applied International Classification of Headache Disorders definitions of postdromal symptoms, and all had high risk of bias. Conclusion Postdromal symptoms in migraine appear to be very commonly reported, but the data are unreliable with regard both to their nature and to how often they occur. Further studies are needed to conclude that they constitute a distinct phase of migraine.